2021
DOI: 10.3390/s21051721
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Vehicle Speed Using Cross-Correlation Algorithms and MEMS Wireless Sensors

Abstract: Traffic information is critical for pavement design, management, and health monitoring. Numerous in-pavement sensors have been developed and installed to collect the traffic volume and loading amplitude. However, limited attention has been paid to the algorithm of vehicle speed estimation. This research focuses on the estimation of the vehicle speed based on a cross-correlation method. A novel wireless micro-electromechanical sensor (MEMS), Smartrock is used to capture the triaxial acceleration, rotation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The GCC algorithm is whitened and pre-weighted in the frequency domain to enhance the suppression of noise interference. The weighting process of the Smoothed Coherent Transform (SCOT) [ 42 ] has a significant suppression effect on noise and is widely used for accurate time delay estimation. The SCOT weighting function is essentially an improvement on the ROTH weighting function [ 17 ], which is expressed as follows: where G x 1 x 1 ( ω ) and G x 2 x 2 ( ω ) are the self-power spectra of transmitted and received signals, respectively.…”
Section: Principle Of Acoustic Ranging and Thermometrymentioning
confidence: 99%
“…The GCC algorithm is whitened and pre-weighted in the frequency domain to enhance the suppression of noise interference. The weighting process of the Smoothed Coherent Transform (SCOT) [ 42 ] has a significant suppression effect on noise and is widely used for accurate time delay estimation. The SCOT weighting function is essentially an improvement on the ROTH weighting function [ 17 ], which is expressed as follows: where G x 1 x 1 ( ω ) and G x 2 x 2 ( ω ) are the self-power spectra of transmitted and received signals, respectively.…”
Section: Principle Of Acoustic Ranging and Thermometrymentioning
confidence: 99%
“…The cross-correlation function describes the degree of correlation between two random signals ( ) x t and ( ) y t at any two different moments 1 t and 2 t , which is defined as Heydari, 2021;Zhang et al, 2021). In this experiment, according to the cross-correlation function between the received signal and the local signal, the time delay estimation of the local sequences and the received sequence can be obtained.…”
Section: Time Delay Estimation Algorithmmentioning
confidence: 99%
“…Compared with the widespread use of SmartRock in the railway industry, the application of SmartRock in asphalt mixtures during compaction is still in the exploratory stage. Limited by the maximum particle size of the asphalt mixture, the researchers reduced the size of the SmartRock [20][21][22][23][24][25]. Wang et al [20] employed a SmartRock embedded into a cold mix asphalt mixture specimen during gyratory compaction to record the aggregate's movement posture change data, and the results of comparing the different SmartRocks' embedded positions demonstrated that the stable-stage characteristics were more prominent when the SmartRock was embedded in the specimen center.…”
Section: Introductionmentioning
confidence: 99%